HUBUNGAN ANTARA MEDIA PEMBELAJARAN INTERAKTIF DENGAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SD NEGERI 3 DELOD PEKEN - Purbayanti, Ni Putu Heny; Suyanta, I Wayan; Prathiwi, Kd Jayanthi Riva (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2026)
This study examined the correlation between the use of PowerPoint- based interactive learning media and Pancasila Education learning outcomes among fourth-grade students at SD Negeri 3 Delod Peken , Tabanan. A quantitative correlational design was employed involving 48 students selected through saturated sampling. Data were collected using questionnaires and document studies , then analyzed through descriptive statistics and the Pearson Product Moment correlation test . The results revealed a significant positive correlation (r = 0.741, p = 0.001), indicating that interactive PowerPoint media contributed to better learning outcomes . The media also enhanced students ’ focus , participation , and motivation during classroom learning .